A uniform cloning platform for mycobacterial genetics and protein production - Arnold, Fabian M. (Sci Rep, 2018)
Molecular research on mycobacteria relies on a multitude of tools for the genetic manipulation of these clinically important bacteria. However, a uniform set of vectors allowing for standardized cloning procedures is not available. Here, we developed a versatile series of mycobacterial vectors for gene deletion, complementation and protein production and purification. The vectors are compatible with fragment exchange (FX) cloning, a recently developed high-throughput cloning principle taking advantage of the type IIS restriction enzyme SapI and its capacity to generate sticky trinucleotide ends outside of its recognition sequence. FX cloning allows for the efficient cloning into an entry vector and the facile transfer of the sequenced insert into a variety of destination vectors. We generated a set of mycobacterial expression vectors spanning a wide range of expression strengths, tagging variants and selection markers to rapidly screen for the optimal expression construct in order to purify membrane proteins from the model organism Mycobacterium smegmatis. Further, we generated a series of suicide vectors containing two counterselection markers and used them to delete twenty genes encoding for potential drug efflux pumps in M. smegmatis. The vectors will further facilitate genetic and biochemical research on various mycobacterial species.